Brain MR Spectroscopic Findings in 3 Consecutive Patients with COVID-19: Preliminary Observations - Rapalino, O.; Weerasekera, A.; Moum, S.J.; Eikermann-Haerter, K.; Edlow, B.L.; Fischer, D.; Torrado-Carvajal, A.; Loggia, M.L.; Mukerji, S.S.; Schaefer, P.W.; Gonzalez, R.G.; Lev, M.H.; et al. (American Journal of Neuroradiology, 2021)
SUMMARY: Brain multivoxel MR spectroscopic imaging was performed in 3 consecutive patients with coronavirus disease 2019 (COVID-19). These included 1 patient with COVID-19-associated necrotizing leukoencephalopathy, another patient who had a recent pulseless electrical activity cardiac arrest with subtle white matter changes, and a patient without frank encephalopathy or a recent severe hypoxic episode. The MR spectroscopic imaging findings were compared with those of 2 patients with white matter pathology not related to Severe Acute Respiratory Syndrome coronavirus 2 infection and a healthy control subject. The NAA reduction, choline elevation, and glutamate/glutamine elevation found in the patient with COVID-19-associated necrotizing leukoencephalopathy and, to a lesser degree, the patient with COVID-19 postcardiac arrest, follow a similar pattern as seen with the patient with delayed posthypoxic leukoencephalopathy. Lactate elevation was most pronounced in the patient with COVID-19 necrotizing leukoencephalopathy.COVID-19coronavirus disease 2019DPLdelayed posthypoxic leukoencephalopathyLaclactatePEApulseless electrical activitySAEsepsis-associated encephalopathySARS-CoV-2Severe Acute Respiratory Syndrome coronavirus 2